(untitled) (MAUSAM, 1970)
The propagation of SH wave was investigated using the velocity distribution function compatible with the actual distribution of shear wave velocity inside the earth. The constants involving the velocity distribution function were calculated from Gutenberg-Birch model and the results discussed.